Effect of Biofertilizer and Inorganic Fertilizer on Growth and Productivity of Shallot (Allium cepa L.) - Tience E. Pakpahan; Taufiq Hidayatullah; Eva Mardiana (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Shallots are categorized as a national priority commodity as a kitchen spice needed every day. Shallots are a commodity that the production continues to increase from year to year. National shallot production increased by 4.9% from 2018 production of 1,502,436 tons and for the North Sumatra region it increased by 7.5% from 2018 production of 113,864 tons (BPS, 2019). This study aims to determine the effect of biofertilizer and inorganic fertilizer on the production of shallots (Allium cepa L.) using mini bulbs and mother bulbs on inceptisol soils in the Practice Field of the Medan Agricultural Development Polytechnic (Polbangtan Medan). This research was conducted from June to October 2021 at Polbangtan Medan. The study used a factorial randomized block design with three replicates and 18 treatment combinations of treatment dosage of organic fertilizer and biofertilizer treatment. Observation parameters in this study were soil analysis, plant height, number of leaves, number of tillers, wet weight, and dry weight. The results of soil analysis on parameters N-total (0.11%) in the low category, C-Organic (0.97%) in the low category, CEC (18.85) in the medium category, pH (7.01) in the neutral category, and Bray II (69.71) high category. This study revealed that the application of biological fertilizer and inorganic fertilizer had no significant effect on all observation parameters, both growth and tuber yield. For the Sanren variety, it is recommended that 5 ml/L of biofertilizer and 75% dose of inorganic fertilizer because it showed the best conditions for the parameters of the number of leaves, wet weight of the sample, and plot. For the Lokananta variety, it is recommended that 10 ml/L of biological fertilizer and 25% dose of inorganic fertilizer because it showed the best conditions for the parameters of plant height, number of leaves, and wet weight of the sample, and plot.